2006
DOI: 10.1007/s11240-005-9044-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability of three economically important micropropagated banana (Musa spp.) cultivars of lower Indo-Gangetic plains, as assessed by RAPD and ISSR markers

Abstract: An efficient micropropagation protocol produced large number of plants of the three elite banana (Musa spp.) cultivars Robusta (AAA), Giant Governor (AAA) and Martaman (AAB) from shoot tip meristem. The genetic relationships and fidelity among the cultivars and micropropagated plants as assessed by random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers, revealed three somaclonal variants from Robusta and three from Giant Governor. A total of 5330 RAPD and 2741 ISSR fragments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 32 publications
2
55
0
4
Order By: Relevance
“…The genetic variation ranged from 0 to 5.6 % after 8 months of culture, which increased to 10 % after 10 years of culture. RAPD and ISSR markers have been used to assess the genetic stability of in vitro-derived plantlets of many other plant species (Ray et al 2006;Kishor and Devi 2009;Aggarval et al 2010;Bhatia et al 2011;Mohanty et al 2011). …”
Section: Molecular Analysismentioning
confidence: 99%
“…The genetic variation ranged from 0 to 5.6 % after 8 months of culture, which increased to 10 % after 10 years of culture. RAPD and ISSR markers have been used to assess the genetic stability of in vitro-derived plantlets of many other plant species (Ray et al 2006;Kishor and Devi 2009;Aggarval et al 2010;Bhatia et al 2011;Mohanty et al 2011). …”
Section: Molecular Analysismentioning
confidence: 99%
“…The Inter Simple Sequence Repeats (ISSR) are DNA-based marker techniques that has been successfully used to determine genetic diversity and relationships Musa germplasms Kaemmer et al, (1992), Howell et al, (1994, Bhat and Jarret (1995), Crouch et al, (2000), Jain et al, (2007), Racharak and Eidathong (2007), Ruangsuttapha et al, (2007), Agoreyo et al,(2008), Brown et al,(2009) and for genome identification, Howell et al, (1994), Pillay et al, (2000), analysis of Musa breeding populations, Crouch et al, (1999), detection of somaclonal variants, Grajal-Martin et al, (1998) and genetic stability, Harirah and Khalid (2006), Ray et al, (2006), Lakshmanan et al, (2007) and Venkatachalam et al,(2007). Using these techniques an unlimited number of polymorphic bands can be produced with relative ease from minute amounts of genomic DNA, Welsh and McClelland(1990), Godwin et al, (1997), Reddy et al, (2002) allowing simultaneous screening of a large number of accessions.…”
Section: Resultsmentioning
confidence: 99%
“…ISSR and RAPD were used in determinate genetic stability of three economically important banana (Musa spp.) cultivars and showed that ISSR detected more polymorphism than RAPD, Ray et al, (2006). Similarly, ISSR were used for detection of genetic uniformity of micropropagated plantlets, Rout et al, (2009) and for screening in vitro mutagenesis and variance Khatri et al, (2011).…”
Section: Resultsmentioning
confidence: 99%
“…In banana, there are reports of somaclonal variation especially in cultivars Williams (AAA) (Damasco et al, 1996;Israeli et al, 1996 Robusta (AAA), and Giant Governor (AAA) (Ray, 2006) in micropropagated plants using different molecular markers. In present study, it was observed that ECS derived plantlets were genetically identical to sucker derived plants especially in cv.…”
Section: Genetic Fidelity Analysismentioning
confidence: 99%